Disaggregate Energy Consumption, Agricultural Output and Economic Growth in Pakistan (The Pakistan Development Review, 2013)
The performance of an economy is generally measured by sustained rise in GDP growth over the period of time. The economic growth is the major goal of macroeconomics. According to neo-classical growth theory, the core factors of growth are labour and capital. In addition to these factors; technological progress, human capital development etc. are the most efficient factors of production. Development of technology and use of mechanisation in production process require energy at massive scale. So, energy has become a crucial factor of economic growth indirectly. Energy is widely regarded as a propelling force behind any economic activity and indeed plays a vital role in enhancing production. Therefore, highly important resources of energy will enhance the technology impact manifold. Quality energy resources can act as facilitator of technology while less worthy resources can dampen the power of new technology. Ojinnaka (1998) argued that the consumption of energy tracks with the national product. Hence, the scale of energy consumption per capita is an important indicator of economic modernisation. In general countries that have higher per capita energy consumption are more developed than those with low level of consumption.